Mapping stunting in Bogor Regency using Web GIS to support the prevention of child growth disorders - Nurkholis; Pria Sukamto (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
Stunting is a chronic nutritional problem that impacts children's physical growth and cognitive development. Although the prevalence of stunting in Bogor Regency shows a downward trend, the distribution of cases across sub-districts remains uneven. This study aims to develop a Web Geographic Information System (Web GIS) application to map and visualize the distribution of stunting based on aggregate data per sub-district. The method used is applied research with a descriptive approach and spatial analysis. This method integrates spatial data on administrative boundaries and non-spatial data on stunting prevalence in 2025 into a web-based system using the Leaflet JavaScript Library. The results show that the system is capable of presenting statistical dashboards, interactive thematic maps, and structured data tables. Classification of stunting levels is carried out using percentage intervals into three categories: low (<5%), moderate (5–7%), and high (>7%). The resulting spatial visualization facilitates the identification of priority areas for treatment more quickly and accurately. Thus, this Web GIS implementation contributes as a spatial-based decision-making support tool in efforts to accelerate stunting reduction.